(untitled) (Vietnam Journal of Community Medicine, 2024)
Dislocation of the total knee arthroplasty (TKA) due to trauma is rare, but open dislocation is even rarer. It can cause serious damage to patients who have had knee replacement. The incidence of dislocation after TKA (both closed and opened) is reported to be only about 0.15% to 0.5%, and it can be associated with serious complications, including joint infection and neurovascular injury. The author reports a case of opened posterior dislocation of the prosthetic knee due to a traffic accident, in a patient 1 month after total knee arthroplasty with tibial plateau bone graft. Although the number of clinical cases is insufficient to establish a treatment giudeline for this rare complication, the author emphasizes the importance of early management and prolonged use of antibiotics to prevent infection.